Solutions of the Kirkwood–Salsburg equation for a lattice classical system of one-dimensional oscillators with positive finite-range many-body interaction potentials - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
For a system of classical one-dimensional oscillators on the d-dimensional hypercubic lattice interacting via pair superstable and many-body positive finite-range potentials, the (lattice) Kirkwood–Salsburg equation is proposed for the first time and is solved.